PENGARUH KOMPETENSI PROFESIONAL DAN EFIKASI GURU TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL (Studi pada guru SMP di Kecamatan Gunungw ungkal) - Rosidi, Imron; Santosa, Agus Budi (Jurnal Ilmiah Telaah Manajemen, 2018)
The teacher quality has often been discussed in Indonesia in the decade and the conclusion remains different. As the cause may raise, factual research is required in regard to teacher condition and another factors affecting teacher performance. This study is conducted to examine the influence of teacher competency, professional as well as efficacy toward the performance as mediated by organizational commitment. This study is conducted with the object to teacher either government officer or non at State Se nior High School on Gunungwungkal District in Pati Regency with number of 105 respondents using census method. Validity test on matrix component, reliability test on alpha cronbach as well as multiple analysis test of Statistical Package for Social Sciences (SPSS) are used as the statistical techniques for this study. The study confirms that professional competence is not in line with organizational commitment, teacher efficacy does not have correlation with organizational commitment whereas professional c ompetence have effects on teacher performance, teacher effectiveness influences on the performance. The professional competence is directly more affecting to teacher performance than organizational commitment variable. Organizational commitment completely mediates the affluence of teacher efficacy towards performance's. Keyword : Professional Competence, Teacher Efficacy, Organizational Commitment, Teacher Performance .